Integrated Coastal Zone Management Status, Challenges and Prospects - Ahlhorn, Frank (Wasser: Ökologie und Bewirtschaftung,, 2018)
This book gives a brief but comprehensive overview of Integrated Coastal Zone Management. Using water management as an example, it enables readers to understand different interests and requirements. It is intended as a textbook for students but can also be used by professionals in administration as well as project management and planning. By summarizing hydrological aspects it clarifies the challenges in water management (e. g. coastal protection, drainage and river management). Further, it presents the principles and methods for integration and good, collaborative processes taking into account the interests and requirements at coastal zones. The book focuses on the status quo in Europe, with examples from The Netherlands, Germany and Spain, and offers up-to-date insights into the state of the art in the United States of America or Australia. The author also takes a fresh look at a number of topics, such as historical reflections. Contents The Coast - Characteristics, Living, Working Historical Annotations and European Developments Basics of Integrated Coastal Zone Management Hydrology of Coastal Regions Sectorial Descriptions Integrated Management Approaches Methodologies of Integration Fictitious Case Studies Audience Students in programs related to coastal issues: civil engineering hydraulics, geosciences, limnology, hydrology, marine biosciences, environmental law, social sciences. Professionals in administration as well as policy and pressure groups. About the Author Dr. Frank Ahlhorn completed doctoral degree at the University of Kiel and is head of Küste und Raum - Ahlhorn & Meyerdirks GbR, a company involved in various aspects of coastal zone management.